Caught between nationalism and transnationalism: how central and east european states respond to east-west emigration - Waterbury, Myra A. (2018)
This article seeks to explain the varied policy responses to the large wave of emigration from Central and Eastern European states during the last two decades, focusing on the cases of Hungary, Bulgaria, Romania, and Poland. Differing degrees of emigrant engagement by these states are explained by the role of internal minorities as active members of the emigrant population and the overall political and demographic relevance of historical kin. This study contributes to our understanding of what shapes state policies towards different types of external populations. It also highlights the particular challenges of state-led transnational engagement in a supranational border regime. - Reproduced.
Keywords: Emigration; European union